1966
DOI: 10.1128/jb.92.2.502-509.1966
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Leptospira pomona and Its Effect on Various Tissue Culture Systems

Abstract: NOR-MAN G. MILLER, AND ROBERTA J. WHITE. Growth of Leptospira pqmona and its effect on various tissue culture systems. J. Bacteriol. 92:502-509. 1966.-Leptospira pomona strain 3341 was grown in association with primary fetal bovine kidney (PBK) and human embryonic skin-muscle fibroblastic (HE) cells in Eagle's minimal essential medium (MEM) with 5% sheep serum. Growth curves of leptospires in PBK and HE cell cultures showed no substantial increase in growth above that obtained in Eagle's MEM in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…When Eagle's medium was supplemented with haemolysed serum, in medium alone or in association with cell lines Clone B or BHK 21, the leptospirae grew abundantly. The latter results are very similar to those obtained by Miller et al (1966) in the culture of serotype pomone in Eagle's medium, with primary foetal bovine kidney and human embryonic skin muscle fibroblast cell cultures-Eagle's medium supplemented with non-haemolysed serum produced poor growth in medium alone. In association with cell line Clone B the growth was enhanced but inferior to that obtained in ME medium supplemented with haemolysed serum (with or without tissue cells).…”
Section: Discussionsupporting
confidence: 85%
“…When Eagle's medium was supplemented with haemolysed serum, in medium alone or in association with cell lines Clone B or BHK 21, the leptospirae grew abundantly. The latter results are very similar to those obtained by Miller et al (1966) in the culture of serotype pomone in Eagle's medium, with primary foetal bovine kidney and human embryonic skin muscle fibroblast cell cultures-Eagle's medium supplemented with non-haemolysed serum produced poor growth in medium alone. In association with cell line Clone B the growth was enhanced but inferior to that obtained in ME medium supplemented with haemolysed serum (with or without tissue cells).…”
Section: Discussionsupporting
confidence: 85%
“…The effect of plasma from infected hamsters on HeLa cells. Earlier studies using whole cultures of virulent leptospires (12,14) as well as CPE factor prepared from culture filtrates (24) showed that a CPE occurred only on fibroblastic but not epithelial cells; consequently it was of interest to determine whether this was also true for cytotoxic factor (CTF).…”
Section: Resultsmentioning
confidence: 99%
“…The selective action of CTF on L cells (fibroblastic) and not HeLa cells (epithelial) correlates with the activity of whole viable leptospires (14) and their products (24) on these cell types. This may be attributed to the affinity of CTF to the mucopolysaccharide on the surface of fibroblastic cells (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…leptospiral cytotoxic factor (108,109). TTie cytotoxic activity has not been characterized, and it is unclear if it is limited solely to virulent organisms.…”
Section: C}totoxin(s) Cytopathic Effects On Certain Cell Cultures Hamentioning
confidence: 99%